Characterization of the most promising fraction of Swietenia macrophylla active against myotoxic phospholipases A2: identification of catechin as one of the active compounds - Lina PRECIADO (Universidad de Antioquia, 2016)
Background: The pharmacological effects produced by snakebite accidents involve the actions of several enzymes, of which those of the phospholipases A2 (PLA2) exhibit a wide variety of effects such as edema and myotoxicity. Some plant extracts have been antagonists of crude snake venoms and toxins. Based on promising bioactivity, Swietenia macrophylla King was selected for further studies. Objective: The purpose of this study was to identify the PLA2 inhibitors present in the crude extract of S. macrophylla that could be promising leads in neutralizing the local effects of ophidian accidents. Methods: Bioassay-guided fractionation of the ethanolic extract of the leaves of S. macrophylla lead to the detection of (+)-catechin, characterized through gas chromatography coupled with mass spectrometry (GC-MS), and confirmed by HPLC. The PLA2 inhibitory activity was measured with the Dole method and a spectrophotometric assay with 4-Nitro-3-octanoyloxy-benzoic acid (4N3OBA). Cytotoxicity was done on C2C12 murine myoblast. Results: Fraction F5 and (+)-Catechin inhibited the PLA2 activity of B. asper venom, in a dose-dependent way. In addition, (+)-Catechin showed an inhibition level of 83.1 ± 3.1 % of the enzymatic activity of one PLA2 purified from the venom of Crotalus durissus cumanensis using 4N3OBA as substrate. Also the ethanolic extract and fraction F5 showed inhibition of the cytotoxicity induced by the Bothrops atrox venom and their Lys 49 PLA2 (80 and 100% respectively). Molecular docking results suggested that that OH from 4´ and 5’ carbons of (+)-catechin could form hydrogen bonds with carboxylate moiety of residue Asp49, while OH from 5 could form a hydrogen bond with Asn 6. Additional Van der Waals interactions were also proposed. Conclusion: Swietenia macrophylla exhibited strong inhibitory activity against PLA2s enzymes. Catechin, the most abundant metabolite in the active fraction F5, is proposed as one of the compounds responsible for the bioactivity.